Legal Review of the Provisions on “Cohabitation” Based on Law Number 1 of 2023 Concerning the Criminal Code - Agus, Azwir (Rechtsvinding, 2025)
Cohabitation or kumpul kebo is a popular term in society to refer to people who live together as husband and wife but are not married or outside of a legal marriage as regulated in Law Number 1 of 2023 concerning the Criminal Code. The research method used is normative juridical or library research, by analyzing library materials or secondary data that are relevant to the topic. This research is descriptive analytical, namely data obtained and processed and analyzed to provide a comprehensive picture of the legal regulations on Cohabitation as regulated in Articles 412, 417, 418, 419 with data collection methods through document studies. The results of the study show that the provisions of the laws and regulations governing cohabitation in the new Criminal Code create legal uncertainty and even lead to the criminalization of all perpetrators of sexual intercourse who are not bound by a legal marriage to become a criminal offense that results in the restriction of a person's individual rights which causes the loss of human rights protection as regulated in the 1945 Constitution.